Physicochemical, rheological and microstructural properties of chicken meat emulsion with the addition of Chinese yam (Dioscorea polystachya) and arrowroot (Maranta arundinacea) as meat substitutes - Ming-Min, Wong; Ismail-Fitry, Mohammad Rashedi (Elsevier, 2023)
This study aimed to produce emulsions formulated with Chinese yam (CY) (Dioscorea polystachya) and arrowroot (AR) (Maranta arundinacea) as potential chicken breast (CB) meat substitutes. Emulsions with 100% CB (control); 50% CB + 50% CY (CY50); 50% CB + 50% AR (AR50); 50% CB + 25% CY + 25% AR (CY25+AR25); 100% CY (CY100); and 100% AR (AR100) were formulated. The emulsion stability, water holding capacity, pH, cooking loss, proximate composition, colour, texture, gel strength, and rheological and microstructural characteristics of different formulations were analysed. The emulsion with 50% arrowroot (AR50) was more stable with lower total fluid released (1.99%), lower fat (2.66%), high protein (8.82%) and fibre (0.62%) contents, and similar moisture (66.17%) content to the control 100% chicken. It had an acceptable texture profile (hardness, 7.38 kg), with a similar colour profile (L∗, 70.22; a∗, 3.47 b∗, 17.41) and a similar appearance to the cooked control image. Furthermore, the rheological and microstructural properties of AR50 were comparable to the control. In conclusion, 50% arrowroot was the best chicken meat substitute and has the potential to be developed into plant-based meat products.